2022
DOI: 10.1038/s41537-022-00315-y
|View full text |Cite
|
Sign up to set email alerts
|

Face pareidolia in male schizophrenia

Abstract: Faces are valuable signals for efficient social interaction. Yet, social cognition including the sensitivity to a coarse face scheme may be deviant in schizophrenia (SZ). Tuning to faces in non-face images such as shadows, grilled toasts, or ink blots is termed face pareidolia. This phenomenon is poorly investigated in SZ. Here face tuning was assessed in 44 male participants with SZ and person-by-person matched controls by using recently created Face-n-Thing images (photographs of non-face objects to a varyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 148 publications
1
13
0
Order By: Relevance
“…As expected from previous behavioral work ( 3 , 10 , 11 ), the impact of display inversion on face response rate was highly significant (face pareidolia with upright orientation, mean ± SD, 0.576 ± 0.171; median (Mdn), 0.612, 95% CI [0.500 to 0.652]; with inversion, 0.363 ± 0.241, Mdn, 0.330, 95% CI [0.256 to 0.470]; Wilcoxon signed-rank test, z = 3.66, P = 0.0003, two-tailed; effect size, eta squared η 2 = 0.61). The difference in face response rate with upright orientation and no-face response rate with display inversion (0.628 ± 0.243, Mdn, 0.656, 95% CI [0.520 to 0.736]) was nonsignificant (Wilcoxon signed-rank test, z = 0.70, P = 0.487, two-tailed; n.s.).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…As expected from previous behavioral work ( 3 , 10 , 11 ), the impact of display inversion on face response rate was highly significant (face pareidolia with upright orientation, mean ± SD, 0.576 ± 0.171; median (Mdn), 0.612, 95% CI [0.500 to 0.652]; with inversion, 0.363 ± 0.241, Mdn, 0.330, 95% CI [0.256 to 0.470]; Wilcoxon signed-rank test, z = 3.66, P = 0.0003, two-tailed; effect size, eta squared η 2 = 0.61). The difference in face response rate with upright orientation and no-face response rate with display inversion (0.628 ± 0.243, Mdn, 0.656, 95% CI [0.520 to 0.736]) was nonsignificant (Wilcoxon signed-rank test, z = 0.70, P = 0.487, two-tailed; n.s.).…”
Section: Resultssupporting
confidence: 87%
“…Face pareidolia is a tendency to see faces in nonface images such as grilled toasts, landscapes, or still-life fruits ( 1 14 ). This ability implies high tuning or a kind of predisposition to a coarse face scheme such as two eyes above a mouth in the visual input ( 10 , 15 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…But beyond the early stages of infancy, it is unclear whether our sensitivity to illusory faces changes across time. Although investigations have shown that susceptibility to face pareidolia varies across individual participants [17,18] and clinical populations [19][20][21][22][23][24][25] there has been no attempt to understand whether this susceptibility is stable across an individual's lifespan.…”
Section: Introductionmentioning
confidence: 99%